A sense of urgency - Kotter, John P., 1947- (Harvard Business Press, 2008)
In his international bestseller "Leading Change," Kotter provided an action plan for implementing successful transformations. Now, he shines the spotlight on the crucial first step in his framework: creating a sense of urgency by getting people to actually see and feel the need for change.